The Archives of the Hudson's Bay Company - Simmons, Deidre (Archivaria, 1996)
The Hudson's Bay Company Archives at the Provincial Archives of Manitoba is indispensable for the study of many aspects of Canadian history and it provides an excellent model for the study of a business archives history. This paper surveys the history of the company's management of its archives from the establishment of the Hudson's Bay Company in 1670 to the present day. A major theme in this history is the problem of access which the archival holdings presented to the company in the twentieth century. With the location of the Archives in London, North American historians were frustrated in their attempts to gain access until a microfilming project with the National Archives of Canada and, eventually, the transfer of the Archives to Winnipeg opened this treasure chest of Canadian history to them. RÉSUMÉ Les archives de la Compagnie de la Baie d'Hudson conservées aux Archives provinciales du Manitoba sont essentielles à l'étude de plusieurs aspects de l'histoire canadienne et fournissent aussi un excellent modèle pour une histoire des archives d'une entreprise. Cet article examine l'histoire de la gestion des archives de la compagnie depuis la fondation de Compagnie de la Baie d'Hudson en 1670 à ce jour. Le problème de l'accès au fonds a constitué un thème majeur de l'histoire de la compagnie au XXe siècle. Comme les archives étaient à Londres, les historiens nord-américains trouvaient difficilement accès à ces archives jusqu'à ce qu'un projet de micro filmage des documents soit mis sur pied par les Archives nationales du Canada et que les documents soient éventuellement transférés à Winnipeg.